If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7b+3-4b=3-3(b
We move all terms to the left:
7b+3-4b-(3-3(b)=0
We add all the numbers together, and all the variables
3b-(3-3b+3=0
| k-1/3=3/6 | | 10.5+p=-8.23 | | 35=-5/4*w | | 8x=45/3 | | 4x-17+3x=18 | | 9=5w-2w | | n*9=0 | | 200=5*(2^x) | | -16=8(u+8)+8u | | 10p-8=12 | | 7x+16=10x-11 | | -29=8(w-8)-3w | | -7(-3y+1)-y=2(y-7)-5 | | 8x-(4x+3)=45 | | 11x-29=3x-15 | | 1/2(2x-4)=19-9x | | 5x-4=-4x+8 | | 3y-21=36 | | 25=3x+4(x+8) | | -2(3y-7)+2y=8+2(7y-3) | | 7x+5-3x=45 | | -33=-(z+15) | | -3v*9=30 | | 6(v-1)=6v+3-3(-4v-3) | | 230=-w+96 | | (x-4)/x-3=1 | | (9x-4)=(5x=16) | | 203-v=23 | | (x-4/x-3)=1 | | b+38/8=7 | | z/9+5-3=10-3 | | 6(u+4)=-4(4u-4)+6u |